Theoretical Review of Scientific Research Work in the Quality of Higher Education Based on Bibliometric Analysis - P. Q. Salibekova; A. E. Kaliyeva; Sh. A. Boluspayev (Экономика: стратегия и практика)
Despite empirical and theoretical research, there is still disagreement over the quality of higher education, and ﬁndings about these links are still far from universal. As a result of the review of the literature, it was found that the quality of higher education can be inﬂuenced by various model characteristics and data sets, assessment methods. In addition, an overview of current research areas and trends in developed countries with a high quality of education was made. This study aims to review scientiﬁc papers to identify key concepts and topics in the ﬁeld of Higher Education. Also, the purpose of the article is to identify gaps in this topic for future research. Bibliometric analysis of literature was carried out using the R-package Biblioshiny tool. The sample includes 181 publications from the Scopus database. The articles are analyzed in relation to annual scientiﬁc products, the most important sources, organizations, compliance network and thematic mapping and evolution to understand trends within the quality of higher education. As a result of the analysis, the main factors aﬀecting the quality of higher education were identiﬁed. The study shows that bibliometric analysis is important for the detailed presentation of theoretical literature and the development of an integrated theoretical basis for the quality of higher education. This review provides guidelines for entering this interdisciplinary ﬁeld.